How the Devil Ray Got Its Horns: The Evolution and Development of Cephalic Lobes in Myliobatid Stingrays (Batoidea: Myliobatidae) - Swenson, John D.; Klomp, Jeff; Fisher, Robert A.; Crow, Karen D. (Frontiers in Ecology and Evolution, 2018)
Manta rays and their relatives of the family Myliobatidae have pectoral fins that have been modified for underwater flight, as well as a pair of fleshy projections at the anterior of the body called cephalic lobes, which are specialized for feeding. As a unique trait with a dedicated function, cephalic lobes offer an excellent opportunity to elucidate the processes by which diverse body plans and features evolve. To shed light on the morphological development and genetic underpinnings of cephalic lobes, we examined paired fin development in cownose rays, which represent the sister taxon to manta rays in the genus Mobula. We find that cephalic lobes develop as anterior pectoral fin domains and lack independent posterior patterning by 5’ HoxD genes and Shh, indicating that cephalic lobes are not independent appendages but rather are modified pectoral fins. In addition, by leveraging interspecies comparative transcriptomics and domain-specific RNA-sequencing, we identify shared expression of anterior patterning genes, including Alx1, Alx4, Pax9, Hoxa13, Hoxa2 and Hoxd4, in the pectoral fins of cownose ray (Rhinoptera bonasus) and little skate (Leucoraja erinacea), providing evidence in support of a homologous relationship between the cephalic lobes of myliobatids and the anterior pectoral fins of skates. We also suggest candidate genes that may be involved in development of myliobatid-specific features, including Omd, which is likely associated with development of thick anterior pectoral fin radials of myliobatids, and Dkk1, which may inhibit tissue outgrowth at the posterior boundary of the developing cephalic lobes. Finally, we observe that cephalic lobes share a surprising number of developmental similarities with another paired fin modification: the claspers of male cartilaginous fishes, including enrichment of Hand2, Hoxa13, and androgen receptor. These results suggest that cephalic lobes may have evolved by co-opting developmental pathways that specify novel domains in paired fins. Taken together, these data on morphological development and comparative gene expression patterns illustrate how distinct body plans and seemingly novel features can arise via subtle changes to existing developmental pathways.